1988
DOI: 10.1103/physrevlett.61.1081
|View full text |Cite
|
Sign up to set email alerts
|

(e,en) Coincidence Studies of the Giant Multipole Resonances ofPb

Abstract: The isoscalar monopole and quadrupole giant multipole resonances of 208 Pb have been studied in the excitation region of 9 to 16 MeV by coincident electron scattering. Concentrations of strength have been found at 10.4 and 14.2 MeV, in reasonable agreement with the predictions of mean-field theory. The measurements reported are the first nuclear-structure investigation carried out by use of the (e,e'n) reaction. Giant multipole resonances are the most important manifestations of collective behavior in atomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…The M"/M~d educed for Pb [16,17] and " Sn [18] are in excellent agreement with the values expected for a pure isoscalar transition to the GQR. Furthermore, the Mz value deduced from an (e, e'n ) measurement [20] on Pb also agrees well with the heavy-ion results.…”
supporting
confidence: 84%
“…The M"/M~d educed for Pb [16,17] and " Sn [18] are in excellent agreement with the values expected for a pure isoscalar transition to the GQR. Furthermore, the Mz value deduced from an (e, e'n ) measurement [20] on Pb also agrees well with the heavy-ion results.…”
supporting
confidence: 84%
“…The coincident detection of neutrons in the hostile environment of an electron accelerator represents a considerable experimental task, and only a few exploratory investigations have been performed [12][13][14][15][16][17]. The present results have been obtained with a new setup for ͑e, e 0 n͒ reactions developed at the S-DALINAC.…”
mentioning
confidence: 72%
“…The latter value represents an unknown mixture of monopole and quadrupole parts. At the photon point the cross section corresponds to B͑E2͒ 1 25 16p B͑E0͒, which can be derived exactly in plane wave Born approximation but should also approximately hold in distorted wave Born approximation [12]. Thus, assuming, e.g., equal exhaustion of the ISGMR and ISGQR, the number given above would translate to 46͑6͒% of the respective EWSR's.…”
mentioning
confidence: 98%
“…therein), both the question of the actual amount of depletion and of the spreading of E2 strength in the region of the GQR needs a precise answer. Furthermore, the situation with respect to the possible discrepancy of GQR strength in single arm (p, p'), (3He, 3He') and (e, c() reactions on one side and (e, e') reactions on the other side turned worse when in a 2~ e'n) coincidence experiment performed at Illinois [12][13][14] it was found that the integrated transition strength observed between Ex = 9-12.5 MeV exhausted 65% of the A T= 0, E2 EWSR, a value essentially in agreement with the inelastic hadron scattering, but in clear disagreement with the (e, e') results.…”
Section: Introductionmentioning
confidence: 93%